2020
DOI: 10.3390/ph13040068
|View full text |Cite
|
Sign up to set email alerts
|

In-Vitro Evaluation of Antioxidant, Antiproliferative and Photo-Protective Activities of Benzimidazolehydrazone Derivatives

Abstract: In the search of multifunctional compounds we designed benzimidazole derivatives endowed with phenolic hydroxy groups and a hydrazone moiety as potential radical-scavenger and the antioxidant agents. The target molecules have been prepared by a simple synthetic procedure and tested for their antioxidant activity by DPPH, FRAP, and ORAC test, for photoprotective activity against UV rays and for antiproliferative activity against Colo-38 melanoma cells. Furthermore, two different dermocosmetic formulations were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…The activity of the synthesized derivatives against DPPH • radical was tested following the Wang et al method [25] modified as previously reported [17]. The results are expressed as μmol TE/g corresponding to an inhibition of the radical equal to 50%, except for some compounds.…”
Section: Dpph Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…The activity of the synthesized derivatives against DPPH • radical was tested following the Wang et al method [25] modified as previously reported [17]. The results are expressed as μmol TE/g corresponding to an inhibition of the radical equal to 50%, except for some compounds.…”
Section: Dpph Assaymentioning
confidence: 99%
“…Cell growth inhibition assays were carried out using two human cell lines, melanoma Colo38 [30,31,17] and keratinocyte HaCat [31,32], cells. Colo 38 cell line was maintained in RPMI 1640, supplemented with 10% fetal bovine serum (FBS), penicillin (100 Units mL-1), streptomycin (100 μg mL-1) and glutamine (2 mM) (complete medium); the pH of the medium was 7.2 and the incubation was performed at 37 °C in a 5% CO 2 atmosphere.…”
Section: Growth Inhibition Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…1). [15][16][17] On the other hand, in our previous paper, 18 we reported the synthesis of a series of benzimidazolyl-2-hydrazones of uoro-, hydroxy-and methoxy-substituted benzaldehydes and 1,3benzodioxole-5-carbaldehyde (Fig. 1).…”
Section: Introductionmentioning
confidence: 95%
“…Hydrazones, as largely nontoxic entities, have attracted significant attention in drug development. They are considered as part of hybrid compounds when designing more effective, often multitarget therapeutics [23–26] . Hydrazones exhibit a broad spectrum of biological activities and have been described in the treatment of tuberculosis, [27] malaria [28] or as antiviral [29,30] and anticancer agents [31] .…”
Section: Introductionmentioning
confidence: 99%